ANTIPLATELET ADEQUACY OF CYCLOPENTYL TRIAZOLOPYRIMIDINE VERSUS CLOPIDOGREL IN-PATIENTS WITH CORONARY HEART DISEASE - Rada, Feryal Hashim (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Ticagrelor, cyclopentyl triazolopyrimidine drug, and Clopidogrel, second-generation thienopyridine drug are antiplatelet drugs indicated for the prevention of thrombotic events in patients with acute or chronic coronary syndromes. The aim of this study is to assess efficacy and safety outcomes of ticagrelor treatment versus Clopidogrel treatment in patients with stable coronary artery disease (stable angina) using maximal platelet aggregation percent (MPAP) method and platelet reactivity index percent (PRIP) method. Methods: A total of 42 patients (27 male and 15 female), their ages ranging (48±8) years with stable angina enrolled from Ibn Albitar Center for Cardiac Surgery for this crossover study. After satisfying, the properties of inclusion criteria they screened for clopidogrel treatment 75 mg daily for 2 weeks than after 2 weeks periods of wash off they treated with ticagrelor 90 mg twice daily for another 2 weeks. Platelet reactivity was tested at baseline (before treatment), after 2 weeks treatment with clopidogrel and after another 2 weeks treatment with ticagrelor. Platelet reactivity measured by light transmittance aggregometry test and by vasodilator-stimulated phosphoprotein (VASP) phosphorylation test. Results: The results of MPAP after 2 weeks treatment with clopidogrel or ticagrelor showed high significant reduction in platelet aggregation in patients with ticagrelor treatment as compared to clopidogrel treatment (30±6% vs. 44±8%). As well, the results of PRIP using VASP-phosphorylation after 2 weeks treatment with clopidogrel or ticagrelor showed high significant reduction in platelet aggregation in patients with ticagrelor treatment as compared to clopidogrel treatment (22±5% vs. 36±7%). Conclusion: Treatment with ticagrelor produced a reduction in platelet reactivity consistent with the reduction in major adverse cardiovascular events and improved survival without increasing major bleeding.